2018
DOI: 10.1002/admt.201800419
|View full text |Cite
|
Sign up to set email alerts
|

3D‐Printed Mechanical Metamaterials with High Energy Absorption

Abstract: Metamaterials [1,[2][3][4] are rational artificial materials with unique structural designs to manipulate and control light, [5] sound, [6,7] mechanical stress, [8,9] etc., leading to previously inacces sible properties in photonic, [10] acoustic, [6] mechanical, [11,12] and many other physical aspects. 3D auxetic materials with highly ordered packing are first observed in the deformation of metallic crystal. [13] To date, the 3D metamaterials facilitate the combinations of mechanical properties that are in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(114 citation statements)
references
References 52 publications
(52 reference statements)
2
112
0
Order By: Relevance
“…Geometrical parameters of meta-structures play crucial role on the structural performance. Several comprehensive research works [23,[34][35][36][37][38][39] were conducted on investigating the effects of geometrical parameters on auxeticity (negative Poisson's ratio) and energy absorption of meta-structures. Yang et al [37] observed that the negative Poisson's ratio increases with increasing re-entrant angle and decreasing horizontal to oblique length ratio.…”
Section: Auxetic Meta-sandwichesmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometrical parameters of meta-structures play crucial role on the structural performance. Several comprehensive research works [23,[34][35][36][37][38][39] were conducted on investigating the effects of geometrical parameters on auxeticity (negative Poisson's ratio) and energy absorption of meta-structures. Yang et al [37] observed that the negative Poisson's ratio increases with increasing re-entrant angle and decreasing horizontal to oblique length ratio.…”
Section: Auxetic Meta-sandwichesmentioning
confidence: 99%
“…Regarding the struts thickness, Wang et al [39] showed that with increase in strut thickness of the re-entrant structure, the auxeticity decreases gradually and finally reaches a plateau while the compression Young's modulus and relative density increase monotonically. It was also proved that the higher the relative density, the larger the energy absorption capacity [34][35]. Hence, increase in strut thickness of the re-entrant auxetic structure results in increase in relative density and therefore increase in energy absorption capacity.…”
Section: Auxetic Meta-sandwichesmentioning
confidence: 99%
“…Polymers 2020, 12, x FOR PEER REVIEW 3 of 17 rapid manufacturing of prototypes [40]. It has great potential to expand for mass manufacturing in acoustic areas.…”
Section: Theoretical and Numerical Methodsmentioning
confidence: 99%
“…The main target frequency range in this study is set as 800-1200 Hz since most of the frequencies of the traffic noises are within this range [40]. The sound absorption at other frequencies can also be reached at the same time as multiple peaks with large absorption coefficients achieved using the multi-layer MPPs.…”
Section: Structural Optimization For Sound Absorptionmentioning
confidence: 99%
See 1 more Smart Citation